Planting system for herbaceous cotton, cultivars Del Cerro and BRS Acala with extra-long fiber, for the Semi-arid region (Research, Society and Development, 2025)
This study aimed to present the agronomic management and productive and technological characteristics of extra-long fiber cotton produced by producers in Peru (cv. Del Cerro) and Brazil (cv. BRS Acala), aiming to encourage and expand its cultivation in the Brazilian Semi-arid region. To this end, a narrative review was chosen, which was carried out through research of bibliographic references in different indexing databases (CAPES Journal Portal, Google Scholar and Scielo), and also in the references of the studies selected to compose this article, always looking for themes related to the culture studied. As it is a proposal for employment and income for the Northeast region, Embrapa Algodão (Cotton) has identified important technological processes related to the production system that enhance yield and improve the quality of cotton Gossypium hirsutum latifolium breed, whose fiber over 36 mm in length manages achieve a high market price. Based on the results obtained for the cultivar BRS Acala in rainfed and irrigated conditions in the trials conducted in the Northeast (BA, RN and CE), their respective yields were 2,719 kg/ha and 4,900 kg/ha, combined with adequate soil preparation and efficient cultural management.